R-PEAKS DETECTION USING WAVELET TECHNOLOGY - Dubrovin, V. I.; Tverdohleb, J. V.; Kharchenko, V. V. (Radio Electronics, Computer Science, Control, 2013)
The given work presents the methodology of R-peaks detection in an electrocardiogram signal based on Discrete Wavelet Transformation. The optimal level decomposition of the detail coefficients can be determined by energy, frequency and cross-correlation analyses. The effectiveness of the proposed algorithm has been tested by using records obtained from the MIT/BIH Physionet arrhythmia database.